Host trait combinations drive abundance and canopy distribution of atmospheric bromeliad assemblages. (18th August 2015) - Chaves, Cleber Juliano Neves; Dyonisio, Júlio César; Rossatto, Davi Rodrigo
Abstract : Anyone interested in plants may already have asked themselves why some trees host a wide diversity and large numbers of epiphytes while others have none. This may occur by chance or could be derived from specific patterns driven by tree traits. Here we evaluated how individual and species characteristics affect the number and location of atmospheric bromeliads. We found that the presence of bromeliads is not stochastic, and that tree traits have a great influence on the presence and abundance of bromeliad species. Additionally, trees can be categorized as worse or better hosts to shelter these plants based on their canopy and trunk characteristics. Abstract: Epiphytes are strongly dependent on the conditions created by their host's traits and a certain degree of specificity is expected between them, even if these species are largely abundant in a series of tree hosts of a given environment, as in the case of atmospheric bromeliads. Despite their considerable abundance in these environments, we hypothesize that stochasticity alone cannot explain the presence and abundance of atmospheric bromeliads on host trees, since host traits could have a greater influence on the establishment of these bromeliads. We used secondary and reforested seasonal forests and three distinct silvicultures to test whether species richness, phylogenetic diversity and functional diversity of trees can predict the differential presence, abundance and distribution of atmospheric bromeliads on hosts. We compared the observed parameters of their assemblage with null models and performed successive variance hierarchic partitions of abundance and distribution of the assemblage to detect the influence of multiple traits of the tree hosts. Our results do not indicate direct relationships between the abundance of atmospheric bromeliads and phylogenetic or functional diversity of trees, but instead indicate that bromeliads occurred on fewer tree species than expected by chance. We distinguished functional tree patterns that can improve or reduce the abundance of atmospheric bromeliads, and change their distribution on branches and trunk. While individual tree traits are related to increased abundance, species traits are related to the canopy distribution of atmospheric bromeliad assemblages. A balance among these tree functional patterns drives the atmospheric bromeliad assemblage of the forest patches.